STRUKTUR PENYAJIAN KESENIAN REJUNG RINGIT DI DESA TANJUNG BULAN KECAMATAN PULAU BERINGIN KABUPATEN OKU SELATAN PROVINSI SUMATERA SELATAN - Hidayatullah, Fadhilah (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
Rejung is one of the local cultures of South Sumatra Province. The form of this art is a rhyme that uses the ethnic language